TEHL simulation model for the tooth flank contact of a single tooth gearbox under mixed friction conditions. (November 2020) - Keller, Michael; Wimmer, Thomas; Bobach, Lars; Bartel, Dirk
Abstract: This work is about the development of a thermal elastohydrodynamic calculation model for the tooth flank contact of the single tooth gearbox. The boundary conditions for load, velocity and flank profiles are precalculated using Finite Element Method modeling. Therefore, it is possible to get macroscopic deformed and distorted tooth flanks for the elastohydrodynamic calculation. A method is provided to remove the Hertzian Deformation of the macroscopic deformed flank profiles, since it should be calculated in conjunction with TEHL simulation. The influence of non-Newtonian and thermal modeling is investigated. Mixed friction is considered based on measured rough surfaces via indirect coupling. An example is given for the impact on the efficiency ratio and power loss, when the gear flanks are adapted. Highlights: The 3D-TEHL tooth flank contact under transient conditions is simulated. Finite Element Method precalculates the profile of loaded teeth. Development of entrainment velocity over time is crucial to friction power loss.